Mean Blood Loss with Prophylactic Tranexamic Acid in females undergoing Cesarean Section - Saima Iqbal, Tahira Akhtar, Ammara Mansoor, Rabia Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obstetric hemorrhage is the most common and dangerous complication encountered during child birth and postpartum hemorrhage accounts for about one-quarter of all maternal deaths globally, especially in developing countries. Tranexamic acid (TXA) with its antifibrinolytic properties, is widely in use for prophylactic treatment of heavy blood loss from trauma, surgery, removal of tooth, bleeding from nose, postpartum bleeding and heavy menstrual bleeding. Aim: To assess the mean blood loss with prophylactic tranexamic acid in females undergoing elective cesarean section Methods: Descriptive case series study conducted in the Department of Obstetrics & Gynecology, DHQ Hospital, Gujranwala from August 2018 to February 2019. After meeting the inclusion criteria 550 females were enrolled. Informed consent and demographic details of the selected females were taken. Then females were given 1g of intravenous TXA 30 minutes before cesarean section. All cesarean sections were done under spinal anesthesia. All included females were followed-up till delivery of the fetus and placenta and blood loss was also noted. SPSS version 21 was applied for data collection and analysis. Results: In this study the mean age of the females was 29.07±6.49 years, 92(16.73%) females were nulliparous. The mean value of BMI was 26.75±4.76 kg/m2. The mean intra-op, post-op and total blood loss of the females was 300.15±29.13 ml, 99.55±29.43 ml & 399.70±41.98 ml respectively. Conclusion: According to this study the total mean blood loss with prophylactic TXA in females undergoing elective cesarean section was 399.70±41.98 ml